(3bUjOI aj (B94 (3HjJkGs
(3ChdgG (B:s
(3HOCJ HGSe Gddg QhMi Hg EgJOJ Edi cTa CSQGQ HHWfg EfWhJ s
(3BNQgG (B:s
(3abGd Ydi hGHf Ye GdeUWai hSQ Ydhe ddNdGFb bO CXgQJ s
(3HgG fXGe GdJYbjHIs
(3cJHJ GdahGUd HGdMeQIs
(3HBNQgG OYGA hWdSes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs